PENGARUH KUALITAS SUMBER DAYA MANUSIA, REGULASI, DAN PERENCANAAN ANGGARAN TERHADAP PENYERAPAN ANGGARAN PADA ORGANISASI PERANGKAT DAERAH PROVINSI PAPUA BARAT - Novita Kristina Mramra; Balthazar Kambuaya; Simson Werimon (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2021)
The research aimed to examine and analyze the effects of the quality of human resources, eulation, and budget planning on the budget absorption in Regional Apparatus Organization of West Papua Province. This research was conduced by partially analyzing the quality of human resources, regulation, and budget planning on budget absorption. In this research used primary data and secondary data. The method of the data collection was the survey using the questionnaires distributed to the respondents. The data were then analyzed using the multiple Regression Statistical Package for the Social Sciences (SPSS).The research results indicated that the quality of human resources had an effects on the budget absorption variable of 0,379 or 37,9%. The regulation had a partial effect on budget absorption variable of 0,371 or 37,1%. Budget planning had a partial effect on budget absorption variable of 0,439 or 43,9%.